2022
DOI: 10.1101/2022.11.27.518065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calculating functional diversity metrics using neighbor-joining trees

Abstract: The study of functional diversity (FD) provides ways to understand phenomena as complex as community assembly or the dynamics of biodiversity change under multiple pressures. Different frameworks are used to quantify FD, either based on dissimilarity matrices (e.g., Rao entropy, functional dendrograms) or multidimensional spaces (e.g. convex hulls, kernel-density hypervolumes). While the first does not enable the measurement of FD within a richness/divergence/regularity framework, or results in the distortion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…We then built a functional dendrogram using a modified version of neighbour-joining clustering [50] based on a Gower dissimilarity distance matrix of the five morphological traits (scaled and centred). This clustering method minimizes functional space distortion [51] and we observed that the functional dendrogram provided a high-quality representation of the distances between species in the Gower dissimilarity distance matrix (0.98, measured by the standardized inverse of mean squared deviation [52], with 1 representing the maximum quality). The functional dendrogram was built using the tree.build function in the ‘BAT’ package [53].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then built a functional dendrogram using a modified version of neighbour-joining clustering [50] based on a Gower dissimilarity distance matrix of the five morphological traits (scaled and centred). This clustering method minimizes functional space distortion [51] and we observed that the functional dendrogram provided a high-quality representation of the distances between species in the Gower dissimilarity distance matrix (0.98, measured by the standardized inverse of mean squared deviation [52], with 1 representing the maximum quality). The functional dendrogram was built using the tree.build function in the ‘BAT’ package [53].…”
Section: Methodsmentioning
confidence: 99%
“…We then built a functional dendrogram using a modified version of neighbour-joining clustering [50] based on a Gower dissimilarity distance matrix of the five morphological traits (scaled and centred). This clustering method minimizes functional space distortion [51] and we observed that the functional dendrogram provided a high-quality representation of the distances between species in the royalsocietypublishing.org/journal/rspb Proc. R. Soc.…”
Section: (D) Species Traits and Phylogenymentioning
confidence: 99%
“…The FD of each ecological group was calculated as a sum of the cophenetic distances between species in the same group on a dendrogram inferred from the three functional traits. We constructed dendrograms using Euclidean distance matrix and neighbour‐joining agglomeration algorithms (Cardoso et al, 2022). α ‐FD was calculated for the entire dataset and for each ecological group separately.…”
Section: Methodsmentioning
confidence: 99%
“…FDUs as nodes of a minimum spanning tree FDM (Ricotta & Moretti, 2008) Ricotta and Moretti (2008) Unweighted FEve (Villéger et al, 2008) FDUs as terminal nodes of a rooted additive tree Sum of path lengths from all terminal nodes to the root (Cardoso et al, 2022) Mean of path lengths from all terminal nodes to the root (Cardoso et al, 2022) Variance of path lengths from all terminal nodes to the root (Cardoso et al, 2022) FDUS as terminal nodes of an unrooted additive tree Sum of branch lengths (Cardoso et al, 2022) Mean of branch lengths (Cardoso et al, 2022) Variance of branch lengths (Cardoso et al, 2022) cases, a technique does exist logically, but it has not yet been used -these are labeled "not yet used". Below, we first provide some information on FDUs and the functional variables describing them, and then the methods are grouped according to components (columns of Table 2).…”
Section: Mean Of Branch Lengthsmentioning
confidence: 99%